(untitled) (Iraqi Journal of Market Research and Consumer Protection, 2026)
This study was conducted at the Rashidiya Date Palm Station, one of the projects of the Horticulture Department/Ministry of Agriculture in Iraq for the 2023 season. This study was aimed to know the effect of benzyl adenine, adding organic fertilizers, and thinning on the yield properties of date palm Cv. Mejhoul. The experiment included three factors. The first factor was the benzyl adenine (B) spray with three concentrations (0, 100, 150 mgL-1). The second factor involved adding humic acid with seaweed extract (HS) to the soil at three levels (0, 1 kg humic acid + 150 g seaweed extract, 2 kg humic acid + 300 g seaweed extract). The third factor was thinning (T) the flower clusters at two levels (without thinning, removing 10 cm from the tips of the flowering clusters with the removal of the central area for branching). The results showed that the T1 B2 F2 treatment had a significant effect on most of the study indicators, such as the average weight, size, length, and diameter of the fruit, average stalk weight, and total yield, with values reaching 36.68 g, 42.00 cm3, 6.66 cm, 3.36 cm, 8.063 kg, and 40.31 kg, respectively, compared to the measurement treatment.